Mechanisms of Pathogenic Candida Species to Evade the Host Complement Attack - Singh, Dhirendra Kumar; Tóth, Renáta; Gácser, Attila (Frontiers in Cellular and Infection Microbiology, 2020)
Candida species are common colonizers of the human skin, vagina, and the gut. As human commensals, Candida species do not cause any notable damage in healthy individuals; however, in certain conditions they can initiate a wide range of diseases such as chronic disseminated candidiasis, endocarditis, vaginitis, meningitis, and endophthalmitis. The incidence of Candida caused infections has increased worldwide, with mortality rates exceeding 70% in certain patient populations. C. albicans, C. glabrata, C. tropicalis, C. parapsilosis, and C. krusei are responsible for more than 90% of Candida-related infections. Interestingly, the host immune response against these closely related fungi varies. As part of the innate immune system, complement proteins play a crucial role in host defense, protecting the host by lysing pathogens or by increasing their phagocytosis by phagocytes through opsonization. This review summarizes interactions of host complement proteins with pathogenic Candida species, including C. albicans and non-albicans Candida species such as C. parapsilosis. We will also highlight the various ways of complement activation, describe the antifungal effects of complement cascades and explore the mechanisms adopted by members of pathogenic Candida species for evading complement attack.